Geometric Design of Highways in USA - Baričević, Hrvoje; Domandžić, Dražen (Promet - Traffic&Transportation, 2012)
This paper describes the criteria, standards, and engineeringprocedures used to design principal elements of the highwayalignment, highway cross sections, and adjacent roadside environment.Development of a comprehensive highway design focuseson the establishment of travel lane configuration, alignmentlocation, and all dimensions related to the highway crosssection. A three-dimensional physical location is determinedthrough calculation of a horizontal and vertical alignment ofthe highway centerline, based on a variety of operational considerations.The results of these activities are refe'ed to as thegeometric design and represent all the visible features of a highwayor street. The first and major portion of the paper deals withthe design of motor-vehicle facilities. Specific design elementsare described and discussed with respect to design methodology.